Crigler Najjar Syndrome [Type II] with Pregnancy: Case Report - Fatima, Bushra; Ahmad, Ayesha; Khan, Tamkin; Ahmad, Rizwan (International Journal of Human and Health Sciences (IJHHS), 2019)
Crigler-Najjar syndromes are rare, autosomal recessive disorders caused by mutations in the genes of bilirubin metabolism. The management of these pregnancies is controversial due to paucity of literature. We discuss here a successfully managed case of pregnancy with Crigler-Najjar Syndrome. International Journal of Human and Health Sciences Vol. 04 No. 01 January’20 Page : 60-62